If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-3)=7(x-1)
We move all terms to the left:
8(x-3)-(7(x-1))=0
We multiply parentheses
8x-(7(x-1))-24=0
We calculate terms in parentheses: -(7(x-1)), so:We get rid of parentheses
7(x-1)
We multiply parentheses
7x-7
Back to the equation:
-(7x-7)
8x-7x+7-24=0
We add all the numbers together, and all the variables
x-17=0
We move all terms containing x to the left, all other terms to the right
x=17
| 5y^2−8y=2 | | 0.30x+0.15(50)=0.15(50) | | (2y+7)2=49 | | 5x(5)+4=4 | | 30/x=x/72 | | 5/6=30/x | | 0.70x+0.20(70)=0.35(36) | | 5a-8=52 | | 8(x+3)+9=2x+6(5+x) | | H=0.75s+3 | | 8(3n-5)=(8n+2)+4 | | 5/6=30/x=x/72 | | -3(t-3)+7t=9t-2 | | 3x2-10x+30=55 | | 6x2+5x=1 | | 1/1.5y=0/25 | | x-3/4+x+8/5=40 | | x^2-(x-2)^2-(28)=0 | | x2-7x-22=-10 | | Y=283-3.5x | | 22=1/2h×11 | | 2x2+2x=0 | | 19x-(9x-2)=12 | | X^2-3x=648 | | -5m^2-7m+12=0 | | 14/35=20/x | | 20/x=14/35 | | 6x/3=20 | | F(n)=5n+9 | | 1/4x+1/5=3(2/3x+1) | | 14x+15=3(23x+1) | | x+6/5+x+4/4=2 |